Fetal Cervical Neuroblastoma: Prenatal Diagnosis. (4th August 2011) - Güzelmansur, Ismail; Aksoy, Hatice Tatar; Hakverdi, Sibel; Seven, Mustafa; Dilmen, Uğur; Dilmen, Gülçin
Abstract : Neuroblastoma is the most frequent extracranial solid tumor in childhood, but it is seldom diagnosed prenatally. It usually presented with adrenal masses. Presentation of other localization is extremely rare. We report a case of cervical neuroblastoma identified at 20 weeks of gestational age. This is the third case diagnosed antenatally on neck region in the literature. Additionally, it is the first case that extended to the brain. We also discussed the literature for cervical neuroblastoma detected prenatally.